LSCF nanopowder from cellulose-glycine-nitrate process and its application in intermediate-temperature solid-oxide fuel cells - Zhou, W.; Shao, Zongping; Ran, R.; Gu, H.; Jin, W.; Xu, N. (Wiley-Blackwell Publishing, Inc., 2008)
Nanostructured La0.6Sr0.4Co0.2Fe 0.8O3-d (LSCF) oxide powder was synthesized by a facile autocombustion process based on a modified glycine-nitrate process (GNP) using cellulose fiber as micro-reactor. As compared with the normal GNP, this novel process allows the combustion to proceed in a much more environmentally friendly and controllable way. The resulted powder is nanocrystallized with particle size of only 15-20 nm as observed by transmission electron microscopy examination. More importantly, because the metal ions could disperse homogenously in cellulose-GN precursor, SrCO3 impurity was effectively suppressed. The concentrations of SrCO3 impurity in LSCF products were determined by carbon dioxide-temperature-programmed desorption technique, which decreased to as low as 1.3 wt% from cellulose-GN process, in contrast to 4.3 wt% from the normal GNP. These features resulted in the attractive improvement of its cathode performance in solid-oxide fuel cells (SOFCs). The interfacial resistances of only ~0.70 and ~0.36 O·cm2 at 600° and 650°C under air, respectively, were observed, which was about two times better than the LSCF cathode derived from the normal GNP. A peak power density of ~346 mW/cm2 was achieved at 600°C with cellulose-GN-derived LSCF cathode based on thin-film Sm0.2Ce0.8O1.9 electrolyte SOFC using 3% humidified H2 as the fuel. © 2008 The American Ceramic Society.